Social determinants and changes in energy drink consumption among adolescents in Norway, 2017–2019: a cross-sectional study - Beate Stokke Solvik; Mads Holten-Andersen (BMJ Open)
Objectives To describe the social determinants and development in energy drink consumption among Norwegian adolescents in 2017, 2018 and 2019.Design Cross-sectional, online, annual, nationwide surveys (Ungdata).Setting Responses collected online from January 2017 to December 2019.Participants Lower and upper secondary school students (n=297 102) aged 12–19 years who responded in 2017, 2018 and 2019.Main outcome measures Frequency of energy drink consumption.Results Over the 3-year period, 66.4% of the men and 41.8% of the women had consumed energy drink once a week or more. The proportion of female high consumers (consuming energy drink more than four times a week) increased from 3.3% to 4.9% between 2017 and 2019; for male, the increase was from 9.8% to 11.5%. In females, the proportion of high consumers increased with 24% (relative risk; CI) (1.24; 1.09 to 1.41) from 2017 to 2018 and 46% (1.46; 1.31 to 1.62) from 2017 to 2019. The corresponding increases in males were 10% (1.10; 1.01 to 1.20) from 2017 to 2018 and 12% (1.12; 1.05 to 1.19) from 2017 to 2019. Any energy drink consumption as well as high energy drink consumption were independently associated with school level, less central residency, low socioeconomic status, physical inactivity and high leisure screen time.Conclusion We found an increase in high consumers among both boys and girls between 2017 and 2019. The observed increase in energy drink consumption among adolescents can explain some of the increased sales of energy drink in Norway.